التحليل الاقتصادي للاحتياجات المائية لمحصول القطن في ظل التغيرات المناخية بمحافظة الدقهلية - شمس الدين، إلهام نسيم حسن (جامعة المنصورة - كلية الزراعة, 2021)
Water is one of the most important basic elements in food production, and there is no doubt that excessive use is a waste of that resource. The problem of the research was the limited water resources and the impact of the agricultural sector on climatic changes, in light of the state’s directives to develop the water-depleting cotton system, which represents an obstacle to the productivity of cotton, which calls for studying the challenge in increasing the production of cotton with the limited water resources in light of climate changes. The research aimed to shed light on the water needs of cotton in light of climatic changes, depending on the cropwat analysis program. It was clear from the results that the cotton area at the level of the Republic and Dakahlia took a general decreasing trend with an annual change rate of about 7.02% and 4.9%, respectively. Water metering at Aswan and the mouths of canals and fields took an increasing general trend with an annual rate of change of about 0.44%, 1.29%, 1.42% in the Republic, and about 0.32%, 1.02%, 1.23% in Dakahlia. The estimated water needs using climatic data during the months of planting the crop in March, April, May, June, July and August were about 124.32, 286.02, 624.96, 698.88, 673.68, 393.36 m3/feddan /month. And by a comparative analysis between the consumed water needs, which amount to about 3109 m3 / feddan, and the estimated water needs, which amount to about 2747.22, It turned out that the water savings amounted to about 18.76 million cubic meters in Dakahlia, achieving a relative difference in the productivity of the water unit. The net return of the water resource amounted to about 12.24%, 12.94%, so that the sacrificed productivity reached about 3.11 thousand tons, and a production loss was estimated at about 9.44 million pounds. The research recommended increasing the area planted with cotton in Dakahlia with the development of varieties that are short-stayed in the soil and resistant to heat and moisture with the speed of lining the canals to avoid deep loss and the necessity of making climatic data available to researchers.
تعتبر المياه من أهم العناصر الأساسية في إنتاج الغذاء، ولا شك أن الإسراف في استخدامه يعد تبديدا لذلك المورد. وتمثلت مشكلة البحث في محدودية الموارد المائية وتأثر القطاع الزراعي بالتغيرات المناخية وذلك في ظل توجيهات الدولة لتطوير منظومة القطن المستنزف للمياه مما يمثل عائقا على إنتاجية القطن وهو ما يستدعي دراسة التحدي في زيادة الإنتاج من القطن مع محدودية الموارد المائية في ظل التغيرات المناخية. واستهدف البحث إلقاء الضوء على الاحتياجات المائية للقطن في ظل التغيرات المناخية معتمدا على برنامج التحليل cropwat. واتضح من النتائج أن مساحة القطن على مستوى الجمهورية والدقهلية أخذت اتجاها عاما متناقصا بمعدل تغير سنوي بلغ نحو 7.02%، 9.4% على الترتيب. وأخذت المقننات المائية عند أسوان وأفمام الترع والحقل اتجاها عاما متزايدا بمعدل تغير سنوي بلغ حوالي 44.0%، 1.29%، 1.42% بالجمهورية، ونحو 0.32%، 1.02%، 1.23% بالدقهلية. وجاءت الاحتياجات المائية المقدرة باستخدام البيانات المناخية في محافظة الدقهلية خلال أشهر زراعة المحصول مارس، أبريل، مايو، يونيو، يوليو، أغسطس بنحو 124.32، 286.02، 624.96، 698.88، 673.68، 393.36 متر مكعب/فدان/شهر. وبالتحليل المقارن بين الاحتياجات المائية المستهلكة والبالغة نحو 3109 متر مكعب/فدان والاحتياجات المائية المقدرة والبالغة حوالي 2747.22 متر مكعب/فدان في محافظة الدقهلية اتضح أن الوفر المائي بلغ نحو 18.76 مليون متر مكعب محققا فرق نسبي لإنتاجية وحدة المياه بلغت نحو 12.24%، وصافي عائد مورد المياه بلغ نحو 12.94% لتصل الإنتاجية المضحي بها حوالي 3.11 ألف طن، وفاقد في الإنتاج قدر بنحو 9.44 مليون جنيه. وأوصى البحث بزيادة المساحة المزروعة بالقطن بالدقهلية مع استنباط أصناف قصيرة المكث بالتربة ومقاومة للحرارة والرطوبة مع سرعة تبطين الترع لتجنب الفقد العميق وضرورة إتاحة البيانات المناخية للباحثين.
Keywords: تحليل الاقتصادي -- الموارد المائية -- محصول القطن -- التغيرات المناخية -- مصر